Lipase catalyzed esterification of formic acid in solvent and solvent-free systems. (July 2019) - Aljawish, Abdulhadi; Heuson, Egon; Bigan, Muriel; Froidevaux, Renato
Abstract: Esterification reaction between formic acid and alcohols (C4, C8) catalyzed by lipases was performed in solvent and solvent-free systems. High Performance Liquid Chromatography (HPLC) was used to study the kinetic parameters (Michaelis-Menten) and the reaction conditions by monitoring the ester synthesis. The optimal conditions for formate ester synthesis were found to be: 0.5 M of formic acid, 1.5 M of alcohol, 2% of Novozym 435 at 40 °C and 400 rpm in acetonitrile solvent without molecular sieves. In solvent-free system, the optimal conditions were found to be: 1 M of formic acid, 10 M of alcohol, 2% of Novozym 435 at 40 °C and 400 rpm without molecular sieves. These optimal conditions resulted in maximum ester yield about 90% for 8 h in solvent system and 5 h in solvent-free system. Among all esterification reactions, the esterification reaction of formic acid with octan-1-ol in solvent-free system was the better regarding the quantity of esterified formic acid, catalytic efficiency of lipase and the required reaction time. Under these optimal conditions, the biocatalyst could be reused for six reaction cycles keeping around 97% of its initial activity after treatment process with n-hexane. Consequently, this enzymatic procedure in solvent-free system could provide formate esters for food and cosmetic applications. Graphical abstract: Image 1 Highlights: Formic acid was esterified by butan-1-ol and octan-1-ol using lipases with and without solvent. The optimal conditions were found to be: 0.5 M of acid, 1.5 M of alcohol, 2% of lipase at 40 °C. Esterification reaction with octan-1-ol in solvent-free system achieved the best result. Lipase could be reused for several reactions after treatment with n-hexane.